THE ANALYSIS OF FACTORS AFFECTING PUBLIC PARTICIPATION IN THE PRACTICE OF ZAKAT COLLECTION AND DISTRIBUTION - Firman Muhammad Abdurrohman Akbar (Indonesia Journal of Zakat and Waqf, 2023)
This study aims to analyze the factors that influence community participation in the practice of collecting and distributing zakat, as well as the factors that influence the distribution of zakat by amil zakat institutions. The analytical method used is discriminant factor analysis. Data was collected through questionnaires which were distributed to 30 respondents in East Jakarta who were selected by purposive sampling technique. The results showed that income and faith factors influenced community participation in the practice of zakat participation, while social and occupational factors influenced the distribution of zakat by amil zakat institutions. Efforts that can be made to increase public awareness regarding the importance of zakat and transparent and accountable management of zakat by amil zakat institutions are by increasing socialization through the mass media, training for administrators of amil zakat institutions, and increasing transparency and accountability in zakat management. This research is expected to contribute to the development of zakat studies and a deeper understanding of the factors that influence community participation in the practice of collecting and distributing zakat.